(untitled) (Revista Brasileira Multidisciplinar, 2010)
Oil and its derivatives are the principal means of energy generation for vehicles that transport raw materials and goods produced in developed and developing regions accentuating the risk of accidents by spills in stockpiling, transport, use or discarding. The contamination by total hydrocarbons suggests the elevated propension to mutations and to the formation of carcinogenic tumors, as a consequence of the exposure to human contamination by these products. This work had as aims: a) To investigate, in a laboratorial scale, the degrading capacity of autochthonous microbiota in the presence of differing concentrations of hydrocarbons (0%, 2,5%, 5% e 7,5%); b) To isolate fungi tolerant to the contaminant; c) To quantify and analyze the biodegradation capacity of soil through the microbial biomass and metabolic quotient; and d) To set, in laboratory, ideal conditions of biodegradation of the xenobiotic compound. Some parameters of microbial activity have been evaluated, such as: biological (Carbon of microbial biomass, CO2 , qCO2 emission, and fungi growth), chemical (pH, electrical conductivity –EC –, analysis of fertility and total hydrocarbons) and physical (physical composition of the soil) for analysis and comparisons. The obtained results suggest that the adding of 5% of waste oil in the ground provided ideal condition for the biodegradation of he contaminant in the environment. From the evaluated parameters, the emission of CO2 and microbial C were considered more indicative of changes in soil microbial activity subject to the addition of hydrocarbons, confirming the possibility of microremediation use.